2021
DOI: 10.1186/s13075-021-02478-y
|View full text |Cite
|
Sign up to set email alerts
|

Change in dietary inflammatory index score is associated with control of long-term rheumatoid arthritis disease activity in a Japanese cohort: the TOMORROW study

Abstract: Background The dietary inflammatory index (DII®), a quantitative measure of the inflammatory potential of daily food and nutrient intake, and associations between a variety of health outcomes have been reported. However, the association between DII score and disease activity of rheumatoid arthritis (RA) is unclear. Therefore, this study was designed to test whether higher DII score contributes to disease activity and as a corollary, whether reducing DII score helps to achieve or maintain low di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 36 publications
3
14
0
Order By: Relevance
“…The results of this cross-sectional study based on the American population showed that whether adjusted or not adjusted covariates, the association between DII and RA was positive, and the risk of RA increased with the increase of DII. This is the same result as the previously published study [22][23] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of this cross-sectional study based on the American population showed that whether adjusted or not adjusted covariates, the association between DII and RA was positive, and the risk of RA increased with the increase of DII. This is the same result as the previously published study [22][23] .…”
Section: Discussionsupporting
confidence: 93%
“…For example, it was reported that DII was positively associated with the risk of colorectal cancer, cancers of the Upper Aerodigestive Tract, gastric cancer, myocardial infarction, obesity, osteoporosis, sarcopenia, and other diseases [16][17][18][19][20][21] . At present, although some studies have shown that there was an association between DII and RA [22][23] , the ethnicity studied was different, and the results of the study are different. Here, we report on the American population enrolled onto a cross-sectional study to further explore the relationship between DII and RA.…”
Section: Introductionmentioning
confidence: 80%
“…To our knowledge, there was limited study conducted on the association of DII score and activity of rheumatoid arthritis disease. Similar to our nding, in a crosssectional and longitudinal study conducted in Japan showed that anti-in ammatory change in DII score was related with low disease activity (24). According to the ndings of a case-control study, adherence to an in ammatory diet such as Western Diet increases the chances of developing RA, while following a healthy diet can reduce the incidence of the disease (25).…”
Section: Discussionsupporting
confidence: 83%
“…High expression of iNOS and COX2 could further induce the production of catabolic factors, including ADAMTS5, MMP1, MMP3, and MMP13, which may lead to damage of the articular cartilage ( Lepetsos et al, 2019 ). Strategies for reducing the level of inflammation have proven to be effective in treating OA ( Matsumoto et al, 2021 ; Zeng et al, 2021 ). In this study, PA significantly reduced the generation of iNOS and COX2 in chondrocytes pretreated with IL-1β.…”
Section: Discussionmentioning
confidence: 99%